Diagnosis Difficulties and Minimally Invasive Treatment for Ovarian Masses in Adolescents - Tarca E; Trandafir LM; Cojocaru E; Costea CF; Rosu ST; Butnariu LI; Iordache AC; Munteanu V; Luca AC (Dove Medical Press, 2022)
Elena Tarca,1,* Laura Mihaela Trandafir,2 Elena Cojocaru,3 Claudia Florida Costea,4 Solange Tamara Rosu,5 Lacramioara Ionela Butnariu,6 Alin Constantin Iordache,7 Valentin Munteanu,8,* Alina Costina Luca2 1Department of Surgery II-Pediatric Surgery, "Grigore T. Popa" University of Medicine and Pharmacy, Iaşi, 700115, Romania; 2Department of Mother and Child Medicine-Pediatrics, "Grigore T. Popa" University of Medicine and Pharmacy, Iaşi, 700115, Romania; 3Department of Morphofunctional Sciences I-Pathology, "Grigore T. Popa" University of Medicine and Pharmacy, Iaşi, 700115, Romania; 4Department of Surgery II-Ophthalmology, "Grigore T. Popa" University of Medicine and Pharmacy, Iaşi, 700115, Romania; 5Department of Nursing, "Grigore T. Popa" University of Medicine and Pharmacy, Iaşi, 700115, Romania; 6Department of Mother and Child Medicine-Genetics, "Grigore T. Popa" University of Medicine and Pharmacy, Iaşi, 700115, Romania; 7Department of Surgery II-Neurosurgery, "Grigore T. Popa" University of Medicine and Pharmacy, Iaşi, 700115, Romania; 8Department of Biomedical Sciences, "Grigore T. Popa" University of Medicine and Pharmacy, Iaşi, 700115, Romania*The authors have equal contributionCorrespondence: Elena Cojocaru; Claudia Florida Costea, "Grigore T. Popa" University of Medicine and Pharmacy, Universității Street No. 16, Iaşi, 700115, Romania, Tel +40765485446, Email elena2.cojocaru@umfiasi.ro; claudia.costea@umfiasi.roAbstract: About 1% of childhood tumors can be malignant ovarian tumors and differential diagnosis with benign ones is sometimes difficult before surgery. Concerning the management of such tumors in adolescents for which future fertility is a concern, there is specific interest in their malignant potential and the possible use of ovarian-sparing operative techniques, as well the suitability of chemotherapy. To exemplify the difficulties of preoperative differential diagnosis, personalized approach and the difficulties of deciding to preserve the affected ovary, we report a rare case of a 14-year-old female adolescent with a growing abdominal painless mass and without any other chronic diseases. After physical examination and imaging investigations, laparoscopic surgical procedure is performed, the peritoneal cavity is explored and the well-delimited gigantic tumor is removed. Considering the normally looking pelvis and absence of adenopathy, as well as the patient's age and wish to have children, both ovaries are preserved. Laparoscopy has become the gold standard in the management of this condition, although there are few studies that report this approach in children; the differential diagnosis between a benign and a malignant tumor cannot be established exactly until after the histological examination, which revealed in our case a cystic teratoma with mature tissues. A better understanding of clinical features and evolution of giant ovarian masses in adolescents could help clinicians better diagnose and treat such lesions.Keywords: cystic teratoma, ovarian tumor, adolescent, fertility